Engineered protein-based functional nanopatterned materials for bio-optical devices. Issue 10 (10th September 2019) - Sanchez-deAlcazar, Daniel; Romera, David; Castro-Smirnov, Jose; Sousaraei, Ahmad; Casado, Santiago; Espasa, Anna; Morant-Miñana, María C.; Hernandez, Jaime J.; Rodríguez, Isabel; Costa, Rubén D.; Cabanillas-Gonzalez, Juan; Martinez, Ramses V.; et al.
Abstract : A simple approach for the fabrication of functional nanopatterned protein materials using protein engineering and soft-nanolithography and its implementation in optical devices based on distributed feedback (DFB) laser phenomena. Abstract : The development of new active biocompatible materials and devices is a current need for their implementation in multiple fields, including the fabrication of implantable devices for biomedical applications and sustainable devices for bio-optics and bio-optoelectronics. This paper describes a simple strategy to use designed proteins to develop protein-based functional materials. Using simple proteins as self-assembling building blocks as a platform for the fabrication of new optically active materials takes previous work one step further towards the design of materials with defined structures and functions using naturally occurring protein materials, such as silk. The proposed fabrication strategy generates thin and flexible nanopatterned protein films by letting the engineered protein elements self-assemble over the surface of an elastomeric stamp with nanoscale features. These nanopatterned protein films are easily transferred onto 3D objects (flat and curved) by moisture-induced adhesion. Additionally, flexible nanopatterned protein films are prepared by incorporating a thin polymeric layer as a back support. Finally, taking advantage of the tunability of the selected protein scaffold, the flexible protein-based surfaces are endowed with optical functions, achieving efficient lasing features. As such, this work enables the simple and cost-effective production of flexible and nanostructured, protein-based, optically active biomaterials and devices over large areas toward emerging applications.